D’un « retour » à l’autre : Religion et spiritualité chez L. Kolakowski, M. de Certeau et M. Foucault - Julien Cavagnis (Cahiers d'Études du Religieux- Recherches Interdisciplinaires, 2016)
This article proposes a comparative reading of the works of Leszek Kolakowski, Michel de Certeau and Michel Foucault with the aim of interrogating the theme of the “return of religion”, which has created a dividing line in French philosophy since the 1980s, based on the alleged idea that since that decade, philosophical enquiry has fortunately begun to deal again with religious issues, after purportedly remaining silent on this topic in the previous era, namely the 1960s and the 1970s. It is obvious that there was no such silence, as the works of Kolakowski, Certeau and Foucault make clear. What is it, then, that the paradigms dominating current philosophical discourses on religion (i.e. the phenomenology of religion and the study of theologico-political issues) reject or prove unable to accept in these approaches, whose very existence they seem to deny ? And what does such a position reveal about those two paradigms themselves ? This paper will first broach the method with which the religious becomes an object of enquiry in the works of Kolakowski, Certeau and Foucault, it will then examine the ways in which these three authors conceptualise religion and it will finally discuss the meaning they endow the mystical or the spiritual within their works.